Sleep and Combat-Related Post Traumatic Stress Disorder (Springer New York, 2018)
There are few clinical problems in the sleep medicine field that are more challenging than the sleep difficulties experienced by individuals suffering from post-traumatic stress disorder (PTSD). This book offers a unique, complete resource addressing all the basic concepts and clinical applications in sleep medicine in settings where combat-related PTSD is commonplace. Authored by leading international experts in the field of sleep/military medicine, Sleep and Combat-Related Post Traumatic Stress Disorder is organized in six sections and provides a broad perspective of the field, from the established theories to the most recent developments in research, including the latest neuroscientific perspectives surrounding sleep and PTSD. The result is a full assessment of sleep in relation to combat-related PTSD and a gold standard volume that is the first of its kind. This comprehensive title will be of great interest to a wide range of clinicians -- from academics and clinicians working within or in partnership with the military health care system to veteran hospital physicians and all health personnel who work with war veterans. .